1971
DOI: 10.1039/df9715200121
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of the coordination and valence of Fe and Mn ions in and on the surface of aluminas and silicas

Abstract: A comparative study of the first-row transition metal ions Fe3+ and Mn2+ on the surfaces of aluminas and silicas has been made using the conventional techniques e.s.r., X-ray diffraction, magnetic susceptibility and in addition a relatively new technique phosphorescence spectroscopy.The results indicate that Fe3+ ions dissolve readily iny-alumina up to 1 w % in samples calcined at 200°C and up to at least 10 % in samples calcined at 800°C. In silica not more than 0.1 w % Fe3+ could be dissolved, the remainder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…It appears, therefore, that the origin of the yellow luminescence in authigenic e-quartz is related to trace elements incorporated during crystallization from oxidizing solutions. However, the observation by Pott and McNicol (1971) of a red luminescence colour with peaks at 695 and 727 nm in quartz containing ferric iron (0.01 to 0.1% Fe 3+) suggests that ferric iron is not the primary cause of yellow luminescence.…”
Section: I(t) = Ixe -T/t1 + I2e -T/t2mentioning
confidence: 98%
See 2 more Smart Citations
“…It appears, therefore, that the origin of the yellow luminescence in authigenic e-quartz is related to trace elements incorporated during crystallization from oxidizing solutions. However, the observation by Pott and McNicol (1971) of a red luminescence colour with peaks at 695 and 727 nm in quartz containing ferric iron (0.01 to 0.1% Fe 3+) suggests that ferric iron is not the primary cause of yellow luminescence.…”
Section: I(t) = Ixe -T/t1 + I2e -T/t2mentioning
confidence: 98%
“…The phenomenon has been attributed to the presence of trace elements (Claffy and Ginther, 1959;Pott and McNicol, 1971;Mitchell and Denure, 1973;Sprunt, 1981), to lattice ordering (Zinkernagel, 1978), to the occurrence of defect centres (Sippel, 1971;Mitchell and Denure, 1973;Jones and Embree, 1976;Koyama et al, 1977;Gee and Kastner, 1980) or to an intrinsic property of the SiO 4 tetrahedron (Hanusiak and White, 1975;Trukhin and Plaudis, 1979). The trace amounts of elements (other than silica and oxygen) incorporated in a-quartz, as well as the chargecompensating exchange of silica by aluminium or iron with hydrogen, lithium, sodium or potassium, and the additional lack of oxygen, are the main reasons for the difficulty in determining the origin of a-quartz luminescence.…”
Section: Origin Of Luminescence Colours In U-quartzmentioning
confidence: 99%
See 1 more Smart Citation
“…Deconvolution indicated that this emission is a composite of at least two emissions at 1.7-1.8 eV and 2.0 eV, which are attributed to Fe 3+ impurities and non-bridging oxygen hole centres (NBOHC) respectively. The substitution of Si 4+ with tetrahedral Fe 3+ , has been associated with emissions at 1.75 eV (Kempe et al, 1999;Pott and McNicol, 1971) and 1.65 eV (Stevens-Kalceff, 2009). Red-IR (1.7 eV) luminescence in feldspar, another framework silicate, has also been linked to tetrahedral Fe 3+ using ESR (Finch and Klein, 1999).…”
Section: The Red Emissionmentioning
confidence: 99%
“…Such a model does not involve changes in the luminescence centre populations, rather that these are now accessible to the excited energy. If we accept the latter model, then luminescence from Fe 3+ centres (Kempe et al, 1999;Pott and McNicol, 1971;Stevens-Kalceff, 2009) may indeed be the cause of the red luminescence, perhaps also associated with NBOHC formation. The contributions to red luminescence from these two types of centre may, in due course, be deconvolved by time-resolved luminescence spectroscopies.…”
mentioning
confidence: 99%